Diet and food insecurity among mothers, infants, and young children in Peru before and during COVID‐19: A panel survey. Issue 3 (11th March 2022) - Pradeilles, Rebecca; Pareja, Rossina; Creed‐Kanashiro, Hilary M.; Griffiths, Paula L.; Holdsworth, Michelle; Verdezoto, Nervo; Eymard‐Duvernay, Sabrina; Landais, Edwige; Stanley, Megan; Rousham, Emily K.
Abstract: The COVID‐19 pandemic may impact diet and nutrition through increased household food insecurity, lack of access to health services, and poorer quality diets. The primary aim of this study is to assess the impact of the pandemic on dietary outcomes of mothers and their infants and young children (IYC) in low‐income urban areas of Peru. We conducted a panel study, with one survey prepandemic ( n = 244) and one survey 9 months after the onset of COVID‐19 ( n = 254). We assessed breastfeeding and complementary feeding indicators and maternal dietary diversity in both surveys. During COVID‐19, we assessed household food insecurity experience and economic impacts of the pandemic on livelihoods; receipt of financial or food assistance, and uptake of health services. Almost all respondents (98.0%) reported adverse economic impacts due to the pandemic and 46.9% of households were at risk of moderate or severe household food insecurity. The proportion of households receiving government food assistance nearly doubled between the two surveys (36.5%–59.5%). Dietary indicators, however, did not worsen in mothers or IYC. Positive changes included an increase in exclusive breastfeeding <6 months (24.2%–39.0%, p < 0.008) and a decrease in sweet food consumption by IYC (33.1%–18.1%, p = 0.001) and mothers (34.0%–14.6%, p < 0.001). The prevalence of sugar‐sweetened beverage consumption remained high in both mothers (97%) and IYC (78%). In sum, we found dietary indicators had not significantly worsened 9 months into the COVID‐19 pandemic. However, several indicators remain suboptimal and should be targeted in future interventions. Abstract : We aimed to assess whether the COVID‐19 pandemic influenced diets of mothers and infants and young children (IYC) in two low‐income urban areas of Peru. We found that, compared to prepandemic data, maternal and IYC dietary indicators had not significantly worsened nine months into the pandemic. A high proportion of households received food assistance or government cash transfers during the pandemic which may have contributed to the stability of dietary indicators. However, indicators such as sweet food consumption (despite reducing during the pandemic) and sugar‐sweetened beverages remained high across the two time periods and should be targeted in future interventions. Key messages: Almost all respondents (98.0%) reported negative economic impacts on their households from the pandemic. During the pandemic, almost half of households (46.9%) were at risk of moderate or severe household food insecurity. During the pandemic, 66.9% of households received cash transfers, and 59.4% received food assistance from the government. Nine months into the pandemic, positive changes included an increased prevalence of exclusive breastfeeding <6 months, a decreased proportion of mothers and infants and young children (IYC) consuming sweet foods, and stable dietary indicators for IYC and women. Consumption of sugar‐sweetened beverages and unhealthy foods remained high across the two time periods for mothers and IYC and should be targeted in future interventions.